Ocular emergencies presenting to an emergency department in Central Spain from 2013 to 2018 - Galindo-Ferreiro, Alicia; Sanchez-Tocino, Hortensia; Varela-Conde, Yago; Diez-Montero, Cecilia; Belani-Raju, Minal; García-Sanz, Raquel; Diego-Alonso, Miguel; LLorente-Gonzalez, Ines; Pazó-Jaudenes, Carlota; Schellini, Silvana [UNESP] (SAGE Publications, 2019)
Purpose: To determine the frequency of ocular conditions among patients presenting to an emergency department at a tertiary hospital in Spain. Methods: A retrospective, longitudinal analysis of all patients who presented to the ocular emergency department of Rio Hortega University Hospital, Valladolid, Spain, from 2013 to 2018 was performed. Data on demographics, ophthalmic examination, and diagnosis were collected. Diseases were classified according the International Classification of Diseases, Ninth Revision, Clinical Modification codes. Results: We had 20,822 patients, of which 10,878 (52.2%) were women. The main age categories were 45–65 years (7391 patients; 35.5%) and 15–45 years (5979 patients; 28.2%). Most of the patients (17,793; 85.5%) were discharged on the same day. Conjunctival pathology was the most common cause of presentation (4110; 19.7%), followed by corneal disorders (4025; 19.3%). Acute conjunctivitis was diagnosed in 2920 (14%) and ocular trauma in 2125 (10.2%) patients. Non-emergency ophthalmic conditions were diagnosed in 1581 (7.6%) patients. Retinal detachments and peripheral holes occurred more commonly in patients aged 45–65 years (p <0.001). Corneal or conjunctival disorders and lid inflammation (p <0.001) were more frequent in women, whereas men had higher incidences of trauma (p <0.001). Conclusion: Most of our patients presented ocular surface diseases. Men were more vulnerable to trauma, mainly superficial foreign body. The majority of the patients presented with uncomplicated ocular conditions that would be managed more cost-effectively by primary health care providers. We advocate greater education of primary care physicians and patients in managing simple ocular emergencies to reduce the cases presenting to an emergency department of a tertiary hospital.
Keywords: conjunctivitis; corneal diseases; emergency; eye care; Ocular emergency